Evaluation of Curriculum Localization Approach in Master's Degree of Curriculum Planning Filed Based on Klein Model - Esfandiyari, Yadolah (2020)
In recent years, the evolution plan in the educational system and curriculum has been one of the most important topics in educational circles. This implies that the programs implemented in higher educational system have not been fully achieved for various reasons. One of the most important reasons is "not paying attention to the localization approach in the curriculum". Curriculum planning is one of the interdisciplines that can play an important role in influencing the curriculum process of humanities. However, the lack of a suitable native curriculum model has made it increasingly dependent on foreign sources and plenty of used terms are imported and translated, resulting in little attention to customs, culture, social, economic and political conditions of society. Although our culture and civilization derive from the most complete and highest order of divine teaching, the educational system has failed to provide an appropriate educational model that is appropriate to cultural conditions throughout the country. The present study has evaluated localization approach of Master's Degree in Curriculum Planning from the viewpoints of faculty members of public universities in Tehran in 2017-2018 academic year. To achieve the research purpose, the main question is "How is desirable of consideration the curriculum localization approach in curriculum planning field based on nine elements of Klein"? This research is descriptive-survey research. The questionnaire has been used for data collection. The statistical population of this study consists faculty members of educational sciences field and have been used Krejcie and Morgan sampling method. Descriptive and inferential statistical methods were used for data analysis. The results of evaluated elements showed that faculty members of Tehran state university ranked elements learning activities, teaching methods, time, materials and resources, grouping, place, and evaluation at a relatively desirable level and target and content elements as undesirable level.